2017
DOI: 10.1371/journal.pone.0183899
|View full text |Cite
|
Sign up to set email alerts
|

Semi-quantitative MALDI-TOF for antimicrobial susceptibility testing in Staphylococcus aureus

Abstract: Antibiotic resistant bacterial infections are a significant problem in the healthcare setting, in many cases requiring the rapid administration of appropriate and effective antibiotic therapy. Diagnostic assays capable of quickly and accurately determining the pathogen resistance profile are therefore crucial to initiate or modify care. Matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (MS) is a standard method for species identification in many clinical microbiology labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 22 publications
1
20
0
2
Order By: Relevance
“…Standard AFST by microdilution methods takes at least 24 h, but the application of MALDI-TOF MS may accelerate susceptibility testing. So far, rapid susceptibility testing by MALDI-TOF MS has mainly been described for bacteria (23,27,(30)(31)(32)(33). One research group has reported on a rapid AFST approach by analyzing the similarities of the MALDI-TOF MS profile spectra derived from different setups containing increasing antibiotic concentrations (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard AFST by microdilution methods takes at least 24 h, but the application of MALDI-TOF MS may accelerate susceptibility testing. So far, rapid susceptibility testing by MALDI-TOF MS has mainly been described for bacteria (23,27,(30)(31)(32)(33). One research group has reported on a rapid AFST approach by analyzing the similarities of the MALDI-TOF MS profile spectra derived from different setups containing increasing antibiotic concentrations (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…MBT ASTRA is a semiquantitative method that was first applied for the detection of meropenem susceptibility in bacteria derived from culture plates or from positive blood cultures within 1 to 4 h (32). Subsequently, additional studies demonstrating the successful applicability of MBT ASTRA for detection of strains resistant to gentamicin, cefotaxime (37), and rifampin (31,38) were performed. In all these studies, the time to the result was significantly reduced from at least 24 h to 3 to 6 h by use of the MALDI-TOF MS approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, the first attempts to use mass spectrometry for micro-organism identification date back to 1975 (Anhalt and Fenselau 1975). In recent years, MALDI-TOF MS has been introduced into clinical microbiology laboratories as a time-and cost-saving method based on the determination of mass/charge (m/z) ratio and strain differentiation using their ribosomal proteins (Maxson et al 2017). MALDI-TOF MS does not depend on metabolic activity and can directly identify within minutes colonies of Gram-positive and Gram-negative bacteria and yeasts grown on agar plates (Wieser et al 2012).…”
Section: Maldi-tof Msmentioning
confidence: 99%
“…The assay yielded almost 100% sensitivity and specificity for all antibiotics evaluated, with poorer results for piperacillintazobactam. Identification of bacteria and analysis of susceptibility are possible within 4 h. In another study, Maxson et al applied this method for the first time to study the susceptibilities of 35 S. aureus isolates to several antibiotics, such as ciprofloxacin, oxacillin, cefepime, and vancomycin (116). The incubation time was established as 2 h, and the resistance breakpoints for classifying the isolates were based on current guidelines from the CLSI (117).…”
Section: Quantitative Resistance Profilementioning
confidence: 99%